Implementation of the P̄ANDA Planar-GEM tracking detector in Monte Carlo simulations - Divani Veis, Nazila; Ehret, Andre; Firoozabadi, Mohammad M.; Karabowicz, Radoslaw; Maas, Frank; Saito, Nami; Saito, Takehiko R.; Voss, Bernd (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2018)
The P¯ANDA experiment at FAIR will be performed to investigate different aspects of hadron physics using anti-proton beams interacting with a fixed nuclear target. The experimental setup consists of a complex series of detector components covering a large solid angle. A detector with a gaseous active media equipped with gas electron multiplier (GEM) technique will be employed to measure tracks of charged particles at forward direction in order to achieve a high momentum resolution. In this work, a full setup of the GEM tracking detector has been implemented in the PANDA Monte Carlo simulation package (PandaRoot) based on the current technical and conceptual design, and the expected performance of the PANDA GEM-tracking detector has been investigated. Furthermore, material-budget studies in terms of the radiation length of the PANDA GEM-tracking detector have been made in order to investigate the effect of the detector materials and its associated structures to particle measurements.
Available online 31 October 2017
Gesehen am 21.04.2020